EFFICIENCY AND UNIFORMITY OF AN SUBSURFACE DRIP IRRIGATION SYSTEM IN SUGARCANE CROP - Ferreira dos Santos, José Wibison; Sampaio Reis, Lígia; Dos Santos Dias, Mirandy; Silva dos Santos, Rilbson Henrique; de Assis da Silva, Francisco; de Oliveira Santos, João Paulo (REVISTA DE AGRICULTURA NEOTROPICAL, 2022)
Agricultural productivity in irrigated areas depends on several factors, including the design and maintenance of irrigation systems. Excessive or insufficient applications of water affect plant growth and development, hence agricultural productivity. For this reason, the evaluation of the irrigation system is essential to avoid water loss during application. This study aimed to evaluate the efficiency and uniformity of a subsurface drip irrigation system in sugarcane crops in an area of the company Usina Coruripe, Alagoas, Brazil. For data collection, the flow rates were obtained in four points along the lateral line, in the first dripper, in the drippers located at 1/3 and 2/3 of the lateral line length, and in the last dripper of each operational unit of the irrigation project. In each row, four emitters were evaluated, totalizing 16 emitters, using a chronometer, collectors, and a measuring cylinder for data collection. In these emitters, the volume of water was collected for 3 minutes, with three repetitions. Christiansen's uniformity coefficient, distribution uniformity coefficient, statistical uniformity coefficient, Hart's uniformity coefficient, and application efficiency were estimated. The irrigation system was considered excellent for distribution uniformity. The application efficiency was classified as acceptable, with an average value of 88.9%. However, despite the application efficiency being classified as acceptable, periodic evaluations of the system are recommended.